2015
DOI: 10.5194/hess-19-3857-2015
|View full text |Cite
|
Sign up to set email alerts
|

Computation of vertically averaged velocities in irregular sections of straight channels

Abstract: Abstract. Two new methods for vertically averaged velocity computation are presented, validated and compared with other available formulas. The first method derives from the well-known Huthoff algorithm, which is first shown to be dependent on the way the river cross section is discretized into several subsections. The second method assumes the vertically averaged longitudinal velocity to be a function only of the friction factor and of the so-called "local hydraulic radius", computed as the ratio between the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The initial condition is η = 0, and L(h km ) in Equation (20) is the water surface width corresponding to h km . After some simple manipulations, it can be shown that Equations (18) and (19) are kinematic, with only one characteristic line passing through each (x, t) point [14,18]. The prediction PDE system is equivalent to a single non-linear convection equation, the function of the gradient of the piezometric head at time level t k , while the correction system has the functional characteristics of a pure diffusive problem.…”
Section: The Fractional Time Step Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial condition is η = 0, and L(h km ) in Equation (20) is the water surface width corresponding to h km . After some simple manipulations, it can be shown that Equations (18) and (19) are kinematic, with only one characteristic line passing through each (x, t) point [14,18]. The prediction PDE system is equivalent to a single non-linear convection equation, the function of the gradient of the piezometric head at time level t k , while the correction system has the functional characteristics of a pure diffusive problem.…”
Section: The Fractional Time Step Proceduresmentioning
confidence: 99%
“…In the present physical problem, an exact scalar potential of the flow field does exist (the water level), and this allows an easy ordering of the computational cells, from the highest to the lowest water levels. After integration in space, the differential form of the prediction Systems (18) and (19) for cell i is: where summation on the l.h.s. represents the leaving fluxes from cell i to any neighboring downstream (in the potential scale) cell j (with H k i ą H k j ) and summation on the r.h.s.…”
Section: Solution Of the Prediction Stepmentioning
confidence: 99%
See 1 more Smart Citation
“…Conveyance K is computed as function of the Manning coefficient n, the geometry of the river section and the water depth h, according to [6]. The investigated reach is discretized in N − 1 channels, linking N sections at the centre of N computational cells.…”
Section: Model 1: Complete 1d Modelmentioning
confidence: 99%
“…In the last years, some researchers have developed indirect methods for the discharge hydrograph estimation, based on the measure of two stage hydrographs at the ends of a selected reach of the river and on the use of unsteady-state hydraulic modeling [4][5][6][7]. The main advantage of the method is that it allows the simultaneous estimation of the unknown river bed parameters and discharge hydrographs.…”
Section: Introductionmentioning
confidence: 99%